4(x-2)+1=x-6+3x

Simple and best practice solution for 4(x-2)+1=x-6+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-2)+1=x-6+3x equation:


Simplifying
4(x + -2) + 1 = x + -6 + 3x

Reorder the terms:
4(-2 + x) + 1 = x + -6 + 3x
(-2 * 4 + x * 4) + 1 = x + -6 + 3x
(-8 + 4x) + 1 = x + -6 + 3x

Reorder the terms:
-8 + 1 + 4x = x + -6 + 3x

Combine like terms: -8 + 1 = -7
-7 + 4x = x + -6 + 3x

Reorder the terms:
-7 + 4x = -6 + x + 3x

Combine like terms: x + 3x = 4x
-7 + 4x = -6 + 4x

Add '-4x' to each side of the equation.
-7 + 4x + -4x = -6 + 4x + -4x

Combine like terms: 4x + -4x = 0
-7 + 0 = -6 + 4x + -4x
-7 = -6 + 4x + -4x

Combine like terms: 4x + -4x = 0
-7 = -6 + 0
-7 = -6

Solving
-7 = -6

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 2x-8=4x-6 | | 3.2+-4d=2.3d+3 | | 6-8x=5x-8x-14 | | -18-11r=24 | | (2x)-1/5=3 | | 7-m=10 | | 2=(x+5)/7 | | 3-x/2=6 | | 3x-28=-20+4x | | 10q-2=2q+6q+10 | | 55y=27(2y+3) | | 3c-4c+1=5c+5 | | 3c-7(-c+4)=-2(c-5)+6 | | 4(1.5c+6)-26c=-9 | | 0.5x+9=17 | | -55-11x=23-8x | | -11b+4=-40 | | 8xy+4xy+3xy^2= | | 10z-3=20x+2 | | (5+4x)(1+x)= | | 3x+2(x-4)=4(x-1) | | y^2=by | | 6x+1=x-8 | | 4x+7y+2x+4y=180 | | 0.36p+0.26=386 | | -2t+22=10 | | -2+4w=14 | | 14(9-7)+x=30 | | 4g+8=2g+14 | | 5(1+4b)-3=-118 | | .25(4r-8)=r-2 | | 3z=12-33 |

Equations solver categories